2020
DOI: 10.1096/fj.202001443rr
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the β‐barrel assembly machine recognizing outer membrane protein substrates

Abstract: β‐barrel outer membrane proteins (β‐OMPs) play critical roles in nutrition acquisition, protein import/export, and other fundamental biological processes. The assembly of β‐OMPs in Gram‐negative bacteria is mediated by the β‐barrel assembly machinery (BAM) complex, yet its precise mechanism remains elusive. Here, we report two structures of the BAM complex in detergents and in nanodisks, and two crystal structures of the BAM complex with bound substrates. Structural analysis indicates that the membrane composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 66 publications
(164 reference statements)
7
46
0
Order By: Relevance
“…The difference between eL1 conformations in the two BAM-LL structures is striking, and suggests that this region must be highly malleable to allow disulfide bond formation within the BamA β-barrel. Interestingly, the 'contorted open' BAM-LL structure closely resembles a recent structure of WT BAM in saposin nanodiscs 22 in which eL1 adopts this inward conformation in the absence of disulfide tethering. In accord with this idea, eL1 can adopt a wide range of conformations in lateralopen BAM structures (Supplementary Fig.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…The difference between eL1 conformations in the two BAM-LL structures is striking, and suggests that this region must be highly malleable to allow disulfide bond formation within the BamA β-barrel. Interestingly, the 'contorted open' BAM-LL structure closely resembles a recent structure of WT BAM in saposin nanodiscs 22 in which eL1 adopts this inward conformation in the absence of disulfide tethering. In accord with this idea, eL1 can adopt a wide range of conformations in lateralopen BAM structures (Supplementary Fig.…”
Section: Resultssupporting
confidence: 58%
“…Here, we have used structural, biochemical and kinetic refolding analyses to dissect these two roles, at least for the 8-stranded OMPs, tOmpA and OmpX. BAM is well-known to be conformationally dynamic, with cryo-EM and X-ray structures capturing the complex in lateral-open 5,6,8 and lateral-closed 6,7,21,22 conformations, and a recent cryoEM, MD and single-molecule FRET study demonstrating dynamics of the complex in nanodiscs 18 . Furthermore, recent X-ray structures have demonstrated that the C-terminal strand of the OMP substrates OmpA and OmpLA forms an antiparallel β-strand pairing with lateralclosed BamA β1, possibly capturing an early stage intermediate in OMP assembly 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations